Compaction of α"-Fe16N2 particles by high-pressure treatment at several gigapascals. (May 2023) - Oka, K.; Ogawa, T.; Yamamoto, H.; Sakaguchi, C.; Gallage, R.; Kobayashi, N.; Azuma, M.
Abstract: Demands for a high-performance magnet that is rare earth-free and composed of abundant elements is increasing. α"- Fe16 N2 is one of the possible candidates for permanent magnet material superior to ferrite and Al-Ni-Co magnets. The resulting α"- Fe16 N2 powder should be made into a high-density bulk to obtain high magnetic properties. Here, we applied high-pressure (HP) and high-temperature (HT) treatment for compaction of α"- Fe16 N2 powders. Our study revealed that HP treatment in the range of 1 to 3 GPa with moderate temperature gives dense α"- Fe16 N2 pellets. We also found that the pelletized sample maintained its magnetic properties for 100 days due to the suppression of gradual decomposition in the air. Graphical abstract: Image, graphical abstract